2016
DOI: 10.1038/aps.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 combined with CCL19 as a nasal adjuvant enhances the immunogenicity of an anti-caries DNA vaccine in rodents

Abstract: A nasal adjuvant consisting of a combination of CCL17 and CCL19 attracts more mature DCs to secondary lymphoid tissues, inducing enhanced antibody responses against the anti-caries DNA vaccine pCIA-P and reducing S mutans infection in rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Accumulating evidence indicates that, during immune response, antigen‐loaded dendritic cells enter the lymphatic vessels by releasing molecules that induce disruption of VE‐cadherin trans dimer‐mediated intercellular adhesion (“button”) between lymphatic lining cells. These molecules are groups of CRS motif‐containing growth factors (e.g., the PDGF superfamily) (Achen et al, ; Boensch et al,, ; Houck et al, ; Joukov et al, ; LaRochelle et al, ; Ostman et al, ; Pollock & Richardson, ;) and cytokines (e.g., IGFBP‐3, CCL1, CCL19, and CCL21) (Alvarez et al, ; Cao, ; Cao et al, ; Das et al, ; Huang et al, ; Johnson & Jackson, ; Lund et al, ; Roberti et al, ; Stacker et al, ; Yan et al, ) which bind to CRSBP‐1 (LYVE‐1) localized to the surface of lymphatic vessels. This stimulates a response, and acts like a token to gain entry to the lymphatic vessel network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence indicates that, during immune response, antigen‐loaded dendritic cells enter the lymphatic vessels by releasing molecules that induce disruption of VE‐cadherin trans dimer‐mediated intercellular adhesion (“button”) between lymphatic lining cells. These molecules are groups of CRS motif‐containing growth factors (e.g., the PDGF superfamily) (Achen et al, ; Boensch et al,, ; Houck et al, ; Joukov et al, ; LaRochelle et al, ; Ostman et al, ; Pollock & Richardson, ;) and cytokines (e.g., IGFBP‐3, CCL1, CCL19, and CCL21) (Alvarez et al, ; Cao, ; Cao et al, ; Das et al, ; Huang et al, ; Johnson & Jackson, ; Lund et al, ; Roberti et al, ; Stacker et al, ; Yan et al, ) which bind to CRSBP‐1 (LYVE‐1) localized to the surface of lymphatic vessels. This stimulates a response, and acts like a token to gain entry to the lymphatic vessel network.…”
Section: Resultsmentioning
confidence: 99%
“…HA does not appear to affect PDGF‐BB binding to CRSBP‐1 (Huang et al, ). We hypothesize that high interstitial concentrations of HA may contribute to the phenotype of lymphedema by blocking the potential attenuating effects of endogenous growth factors/cytokines containing CRS motifs such as PDGF‐BB, VEGF‐A, IGFBP‐3, CCL1, CCL19, CCL21 (Alvarez et al, ; Das et al, ; Hou et al, ; Huang et al, , ; Johnson and Jackson, ; Lund et al, ; Roberti et al, ; Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen-Hoai et al (2012) showed that recombinant plasmid encoding the human CCL19 gene and immunized mouse tumor models with the anti-tumor DNA vaccine pVax/E2A by gene gun, the results showed that CCL19 can enhance protection of vaccine and B cells function as APC. Yan et al (2016) pointed that a nasal adjuvant composed of CCL17 and CCL19 is used together with an anti-caries DNA vaccine, they can recruit more mature DC to secondary lymphoid tissues, induce the body to produce high titer antibodies, and reduce S mutants infection in rodents after vaccination. The results of T and B lymphocyte subsets percent, the expression diff erences of immune-related genes, and the RPS in p-CCL19-injected fi sh also showed that there was no signifi cant diff erence between the p-CCL19 group and the pBudCE4.1 group after immunization (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to explore the effect of nicotine on the cariogenic potential of S. mutans in vivo . Regarding the sample sizes ranged from 6 to 10 rats for each group in most caries studies,29, 30, 31, 32, 33, 34 we took 16 rats and divided them into two groups (n = 8). The results of our study provide striking evidence that nicotine promotes the attachment of S. mutans to dental surface and the development of caries in vivo , and it appears to be a promotion factor for the development of dental caries.…”
Section: Discussionmentioning
confidence: 99%